The role of citrate in plant-pathogen interactions - Hendry, Tia Lynne (Department of Molecular and Cell Biology, 2016)
Bacterial plant pathogens have evolved a wide range of mechanisms to suppress the immune response that they trigger in their hosts, including the production of effectors and phytotoxins. The tri-carboxylic acid citrate, which is secreted into the apoplast by both bacterial pathogens and plant hosts has previously been shown to increase the virulence of the gram negative pathogen Pseudomonas syringae DC3000 (Pst DC3000), by acting both as a chemoattractant and as an inducer of genes associated with the type III secretion system (T3SS) and phytotoxin production. The effect of citrate on the host is less clear, though microarray analysis of Arabidopsis thaliana has demonstrated that application of exogenous citrate leads to the differential expression of 1876 genes suggesting that it might act as a metabolic signal for transcriptional reprogramming. In this study, functional enrichment analysis revealed statistically significant enrichment for gene ontology terms associated with defence in both citrate up-regulated and down-regulated gene sets. Furthermore this project demonstrated that exogenous citrate can increase the success of virulent Pst DC3000 infection in Arabidopsis; bacterial titres in plants pre-treated with citrate 24 hours prior to infection were significantly higher than those in control plants. This phenomenon was also observed in plants pre-treated with a non-metabolisable citrate analogue but not in plants pre-treated with another TCA cycle intermediate, malate, suggesting that it is citrate specific. However, it remains unclear whether the increased apoplastic citrate concentrations lead to increased bacterial titres through a suppressive effect on the host immune response, an enhanced induction of the T3SS system in Pst DC3000, or a combination of both.